Cheating or Surviving: English Students’ Perspectives on Academic Dishonesty as a Strategy to Coping - Eric Gilbran Aditya; Bibit Suhatmady; Maria Teodora Ping; Effendi Limbong (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Academic dishonesty has become a considerable problem within the academy, especially when one considers the emphasis being placed upon ensuring that the student population is able to achieve at a high level. This study is a qualitative case study wherein aim to explore the concept of academic dishonesty from a different point of view, based upon the interviews with English as a Foreign Language (EFL) students from Mulawarman University in Indonesia, exploring their views of academic dishonesty regardless of its negative implications, but rather as a coping strategy for stress and a way to meet the demands of their academic obligations. Through my collection of data in the form of a semi-structured interview of four English Education majors, I have learned that EFL undergraduates do not consider cheating as a total denouncement of hard work, but rather a way of coping with the demands of a tight deadline, heavy responsibilities, and the stress of failing a course, particularly when it is a strategic measure in using artificial intelligence to manage their examinations and alleviate further stress or anxiety. They rationalized their behavior as a common problem within the academic environment.